2014
DOI: 10.1371/journal.pone.0107715
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles of 10 Hz Alpha-Band Power Modulating Engagement and Disengagement of Cortical Networks in a Complex Visual Motion Task

Abstract: Alpha band power, particularly at the 10 Hz frequency, is significantly involved in sensory inhibition, attention modulation, and working memory. However, the interactions between cortical areas and their relationship to the different functional roles of the alpha band oscillations are still poorly understood. Here we examined alpha band power and the cortico-cortical interregional phase synchrony in a psychophysical task involving the detection of an object moving in depth by an observer in forward self-motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 74 publications
2
16
0
1
Order By: Relevance
“…Analogously to the alpha power, which shows an early increase and later decrease, beta power may be involved in the early selection (N1) and later processing of visual information (approx. in the N2 latency; Capilla et al 2014;Rana et al 2014;Güntekin et al 2013; see also Wróbel, 2000). Overall these results show that the amount of resources deployed during early visual processing (N1) is associated with a tendency to inattention.…”
Section: Role Of Intrinsic Oscillatory Activity During Early Visual Pmentioning
confidence: 94%
See 2 more Smart Citations
“…Analogously to the alpha power, which shows an early increase and later decrease, beta power may be involved in the early selection (N1) and later processing of visual information (approx. in the N2 latency; Capilla et al 2014;Rana et al 2014;Güntekin et al 2013; see also Wróbel, 2000). Overall these results show that the amount of resources deployed during early visual processing (N1) is associated with a tendency to inattention.…”
Section: Role Of Intrinsic Oscillatory Activity During Early Visual Pmentioning
confidence: 94%
“…Moreover, alpha, beta, and theta bands during the event-evoked period were also assessed since attentional allocation of resources is thought to play a multi-band (alpha, beta and theta) effect during visual processing (Güntekin, Emek-Savaş, Kurt, Yener, & Başar, 2013;Bastiaansen & Hagoort, 2003;Palva & Palva, 2007;Jensen, Bonnefond, & VanRullen, 2012). ROIs were identified on the basis of previous findings that showed increased alpha power during the period prior the presentation of a stimulus (Yamagishi et al, 2008), but also in the N1 latency and in later processing (>300 ms) in a form of a dissociated alpha band modulation (i.e., early/late alpha enhancement/suppression; Rana & Vaina, 2014;Capilla, Schoffelen, Paterson, Thut, Gross, 2014; see also Palva & Palva, 2007); moreover, modulation in the theta and beta band have also been found to be respectively indicative of good performance (i.e., encoding the location of the target stimulus; Bastiaansen & Hagoort, 2003;Klimesch, 1999) and increased visual attention (Güntekin et al 2013). Hence, the following ROIs were investigated: pre-stimulus alpha Power estimates (in dB) for the bands of interest and the level of saliency (low/high) were submitted to logistic regressions to test whether they were predictive of the level of inattention (similar analyses assessing behavioural performance on the basis of the power estimates of frequency bands can be found in Yamagishi, Callan, Anderson, & Kawato, 2008, for pre-stimulus period; see also Jensen et al 2012, for latency after the on-set of the array).…”
Section: Role Of Intrinsic Oscillatory Activity During Early Visual Pmentioning
confidence: 99%
See 1 more Smart Citation
“…A simultaneous EEG and functional magnetic resonance imaging (fMRI) study has shown that activity of the superior/medial frontal cortex is positively correlated with alpha lateralization by selective attention (Liu, Bengson, Huang, Mangun, & Ding, 2014). Rana and Vaina (2014) reported that alpha activity of frontoparietal areas was increased when controlling spatial attention. Thus, it is predicted that the alpha activity derived from these regions is also modulated by previous trial compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have implicated Alpha band power with the allocation of focused attention, particularly at the 10 Hz frequency (Rana & Vaina, 2014). Participants allocating attention across a variety of modalities show increased Alpha band power associated with the suppression of task-irrelevant information (Foxe & Snyder, 2011).…”
Section: Electroencephalographymentioning
confidence: 99%